1989
DOI: 10.1152/ajpheart.1989.256.6.h1553
|View full text |Cite
|
Sign up to set email alerts
|

An unusual receptor mediates adenosine-induced SA nodal bradycardia in dogs

Abstract: To characterize the receptor mediating the negative chronotropic effect of adenosine in dogs, experiments were performed on conscious dogs with chronically implanted cardiovascular instrumentation. Autonomic blockade was used to eliminate any reflex influences on heart rate. Intravenous bolus injections of various adenosine analogues caused dose-dependent, aminophylline-blockable reductions in heart rate with a potency order of 5'-(N-ethylcarboxyamido)-adenosine (NECA)-78:2-chloroadenosine-17:adenosine-1. Dipy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Our results demonstrate that A 1 AR blockade is not detrimental in this experimental model and does not block IPC induced by multiple ischemia/reperfusion cycles. Although caution is certainly necessary to extrapolate our findings in a dog model to humans, especially since it has been suggested that A 1 ARmediated responses in the dog may differ from that of humans (Belloni et al, 1989;Martin, 1992), our data provide evidence that the use of A 1 AR antagonists as diuretics inpatients with ischemic heart disease may not pose a problem. Dose-relationship studies in additional models will be necessary to address this issue further.…”
Section: Discussionmentioning
confidence: 74%
“…Our results demonstrate that A 1 AR blockade is not detrimental in this experimental model and does not block IPC induced by multiple ischemia/reperfusion cycles. Although caution is certainly necessary to extrapolate our findings in a dog model to humans, especially since it has been suggested that A 1 ARmediated responses in the dog may differ from that of humans (Belloni et al, 1989;Martin, 1992), our data provide evidence that the use of A 1 AR antagonists as diuretics inpatients with ischemic heart disease may not pose a problem. Dose-relationship studies in additional models will be necessary to address this issue further.…”
Section: Discussionmentioning
confidence: 74%
“…This was not changed by Liposyn or glycerol control infusion and therefore was not likely due to the effect of CHA to lower FFA or glycerol. It is possible E635 that CHA had some direct effect on peripheral tissues to increase glucose uptake, perhaps by increasing regional blood flow (3).…”
Section: E634mentioning
confidence: 99%
“…Indeed, some reports have indicated that Ado receptors involved in canine sino-atrial (SA) nodal function in vivo '." Macmillan Press Ltd, 1992 have an unusual order of agonist potency that does not conform to the conventional Al receptor (Belloni et al, 1989a) identified from tissue and binding studies in vitro.…”
Section: Introductionmentioning
confidence: 99%